2015
DOI: 10.1016/j.jom.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in multi‐tier supply chains: Understanding the double agency role of the first‐tier supplier

Abstract: In light of the growing complexity of globally dispersed, multi-tier supply chains, the involvement of first-tier suppliers has become instrumental in the quest for achieving sustainability compliance along the supply chain. We describe this new responsibility as the double agency role. We employ agency and institutional theory arguments to explore the conditions under which first-tier suppliers will act as agents who fulfill the lead firm's sustainability requirements (i.e., the primary agency role) and imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
547
3
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(571 citation statements)
references
References 66 publications
19
547
3
2
Order By: Relevance
“…Therefore, from a risk and compliance perspective, buying firms should consider extending their sustainability strategies and practices to distant tiers further upstream in their supply network (Wilhelm et al, 2016a).…”
Section: Lower Tier Sustainability Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, from a risk and compliance perspective, buying firms should consider extending their sustainability strategies and practices to distant tiers further upstream in their supply network (Wilhelm et al, 2016a).…”
Section: Lower Tier Sustainability Managementmentioning
confidence: 99%
“…While some buying firms interact only with their direct suppliers which act as gatekeepers and help them to approach suppliers at distant tiers (Wilhelm et al, 2016a), other firms approach lower tier suppliers directly to control and monitor their sustainability performance (e.g., Grimm et al, 2016). However, the missing direct business relationship with second-or third-tier suppliers and the resulting opaque supply network structures often cause information deficits for buyers (Busse et al, 2017a).…”
Section: Lower Tier Sustainability Managementmentioning
confidence: 99%
“…Some recent studies have already made an effort in this regard: Fayet and Vermeulen (2014) [153] investigate sustainable standards for smallholder farmers in the Indian multi-tier cotton SC. Bregman et al (2015) [170] examine the relationship between the ethical judgment of firms engaged in GS and consumers' intentions to purchase a firm's products; Wilhelm et al (2016) [171] discuss the double-agency role played by first-tier suppliers in managing sustainability in three-tier SCs, i.e., first-tier suppliers need to first fulfil focal companies' sustainability requirements as an agent, then implement the requirements in their suppliers' operations as a principal.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Distinct social supply chain policies within the textile industry involve not only working conditions and wages, but also housing and home worker conditions. Through the complexity of the textile supply chain, it has been found that there is a need to implement the SSCM strategy towards the sub-tier supplier level [13]. Thus, previous research is concerned with the sustainable management of supply chains, analyzing the textile sector, but, due to the complexity of the issue, there are still various research gaps.…”
Section: Introductionmentioning
confidence: 99%